The relation of spiritual aspect of nutrition and health - Samieefar, Noosha; Golmohammadi, Maryam; Rashedi, Ronak; Rezazadeh, Arezoo; Heidarnia, Mohammad Ali (Social Determinants of Health, 2018)
Background: After centuries paying particular attention to physical health, attention has been attracted to other aspects of human health meaning the psychological, social, and especially spiritual aspect in the past decades. Spiritual aspect of health is the coordinator of other dimensions and improves mental function. Spiritual well-being issues such as halal and haram and food purity should also be considered. Method: This was a cross-sectional study conducted among Shahid Beheshti university staff. Pearson’s correlations were used to calculate variable associations. Linear multiple regression analysis was performed to identify variables contributing to an explanation of different aspects of nutrition and health. Results: 128 personnel participated in this study. Positive correlations were observed between education and total scores of nutrition aspects (r=0.049, p-value<0.05) and attention to physical aspect of nutrition for males (r =0.052, p-value<0.05). Also there is a significant correlation between attention to mental aspect of nutrition and social aspect of nutrition (r=0.740, p-value<0.01). Conclusion: Age, sex and education, are among the factors that may affect the nutritional attitude. Therefore, using different methods to improve the nutritional practice of society considering its dimensions and taking the factors influencing it into account seems to be essential.